Projected impacts to the production of outdoor recreation opportunities across US state park systems due to the adoption of a domestic climate change mitigation policy. Issue 48 (April 2015) - Smith, Jordan W.; Leung, Yu-Fai; Seekamp, Erin; Walden-Schreiner, Chelsey; Miller, Anna B.
Highlights: A technical efficiency model identifies where state park systems can be improved. The technical efficiency model is joined with output of CC policy simulations. Shifts in operating expenditure under the CC mitigation policy are estimated. Results reveal substantial variability across states. Increasing technical efficiency is the best solution to adapt to CC policy impacts. Abstract: Numerous empirical and simulation-based studies have documented or estimated variable impacts to the economic growth of nation states due to the adoption of domestic climate change mitigation policies. However, few studies have been able to empirically link projected changes in economic growth to the provision of public goods and services. In this research, we couple projected changes in economic growth to US states brought about by the adoption of a domestic climate change mitigation policy with a longitudinal panel dataset detailing the production of outdoor recreation opportunities on lands managed in the public interest. Joining empirical data and simulation-based estimates allow us to better understand how the adoption of a domestic climate change mitigation policy would affect the provision of public goods in the future. We first employ a technical efficiency model and metrics to provide decision makers with evidence of specific areas where operational efficiencies within the nation's state park systems can be improved. We then augment the empirical analysis with simulation-based changes in gross state product (GSP) to estimate changes to the states' ability to provide outdoor recreation opportunities from 2014 to 2020; the results reveal substantial variability across states. Finally, we explore two potential solutions (increasing GSP or increasing technical efficiency) for addressing the negative impacts on the states' park systems operating budgets brought about by the adoption of a domestic climate change mitigation policy; the analyses suggest increasing technical efficiency would be the most viable solution if/when the US adopts a greenhouse gas reduction policy.